Historiography of the Problem of Profession-Oriented Differentiation of the Secondary School During the Second Half of 19th Century - Kushnir, Valentyna (Pedagogical Discourse, 2013)
The article deals with the problem of historiography of imperial period, the introduction of profession-oriented differentiation in secondary schools of the Russian Empire during the second half of the 19th century. The works on the history of the school of a general character which highlighted the problem and a number of works of the contemporaries of those changes, their positions in the confrontation between classical and real education are characterized. It has been determined that the historiography of the specified period is an important source of deep diverse knowledge of that sphere. However, it has not created the necessary body of knowledge for generalization of the problem of implementation of profession-oriented differentiation in secondary schools of the Russian Empire during the second half of 19th century, the implementation mechanisms and the adoption of educational changes by the society of that period.